1999
DOI: 10.1093/hmg/8.8.1365
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the Lysosomal  -Mannosidase Gene Results in Mice Resembling a Mild form of Human  -Mannosidosis

Abstract: Alpha-mannosidosis is a lysosomal storage disease with autosomal recessive inheritance caused by a deficiency of the lysosomal alpha-mannosidase, which is involved in the degradation of asparagine-linked carbohydrate cores of glycoproteins. An alpha-mannosidosis mouse model was generated by targeted disruption of the gene for lysosomal alpha-mannosidase. Homozygous mutant animals exhibit alpha-mannosidase enzyme deficiency and elevated urinary secretion of mannose-containing oligosaccharides. Thin-layer chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 40 publications
1
47
0
Order By: Relevance
“…We then assessed whether transgenic knockout mice reflect the human pathology comparable to the conventional alpha‐mannosidase knockout mice15 and are suitable to study the impact of chronic ERT on neuropathology. Therefore, transgenic and nontransgenic knockout mice as well as wild‐type mice were analyzed for storage and secondary pathological changes 8, 16.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We then assessed whether transgenic knockout mice reflect the human pathology comparable to the conventional alpha‐mannosidase knockout mice15 and are suitable to study the impact of chronic ERT on neuropathology. Therefore, transgenic and nontransgenic knockout mice as well as wild‐type mice were analyzed for storage and secondary pathological changes 8, 16.…”
Section: Resultsmentioning
confidence: 99%
“…In this experimental set‐up either nontransgenic wild‐type or nontransgenic heterozygote animals served as controls 15. In previous studies, we demonstrated that four biweekly injections of 500 U/kg rhLAMAN were necessary to significantly reduce CNS storage when applied short term 16.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other lysosomal storage disorders, different, but disease-specific, patterns of neuropathology are characteristic. For example, a-mannosidosis (OMIM 248500), caused by mutations in the a-mannosidase (MAN2B1, EC 3.2.1.24, 609458) gene, has been described in cats, cattle, guinea pigs, humans, and knockout mice (Auclair and Hopwood 2007;Blanz et al 2008;Crawley and Walkley 2007;Damme et al 2011;Stinchi et al 1999;Vite et al 2001) and has somewhat different neurological manifestations and neuropathological characteristics depending on the species. Aspartylglucosaminuria (AGU, OMIM 208400) (Dunder et al 2010;Jalanko et al 1998;Kaartinen et al 1996) is caused by mutations in the gene for glycosylasparaginase (AGA, EC 3.5.1.26, 613228), the enzyme necessary for hydrolysis of the proteinoligosaccharide linkage in N-linked glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…An α-mannosidosis mouse model has been generated by targeted disruption of the gene for MANB (Stinchi et al, 1999). Homozygous mutant mice exhibit enzymatic deficiency and elevated urinary secretion of mannosecontaining oligosaccharides.…”
Section: Animal Modelsmentioning
confidence: 99%